Structure of Time Narration in the Novel "New Egypt" of Nagheeb Mahfouz - Muhammed Sani , Muktar; Ameen, Bashir (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Time is a fundamental element in literature for as long as literature has existed. It's equally useful for showing and understanding the development of plot in a story setting. The objective of this study was to discuss the structure of time narration as adopted by the novelist in "New Egypt". The findings of this study Showed that, time has played a significant role in the novel, it figured prominently in the structure to the extent that, all other components in the novel highly depended on time to perform their functions. It also revealed that the story time and narration time were not compatible, due to the use of analepsis and prolepsis. While narrating the period of events, he employed summary and ellipsis techniques to speed up the narration and filtered out some information that would overburden the narration in details. But while slowing down the narration, he used descriptive pause, to stop the story and give way for commentaries, description and even digression of the narrator. He equally applied scene to delay the narration process to create freedom of expression for some characters to express their perception freely, withering a long passage.